Three bold pixies and other stories - Blyton, Enid; Cloke, Rene (Award London, 1994)
Three Bold Pixies and Other Stories is a whimsical collection of tales about three adventurous pixies who embark on daring escapades in their enchanted world. Each story showcases the pixies' boldness and cleverness as they face challenges, outwit tricky foes, and help their friends along the way. With imaginative plots and endearing characters, the stories emphasize the values of courage, teamwork, and friendship. Filled with magic and wonder, this collection is perfect for young readers who enjoy fantastical adventures in a magical realm.